Microphysics of Cosmic Plasmas - Balogh, André; Bykov, Andrei; Cargill, Peter; Dendy, Richard; Dudok de Wit, Thierry; Raymond, John (Space Sciences Series of ISSI, 2014)
This title presents a review of the detailed aspects of the physical processes that underlie the observed properties, structures and dynamics of cosmic plasmas. An assessment of the status of understanding of microscale processes in all astrophysical collisionless plasmas is provided. The topics discussed include  turbulence in astrophysical and solar system plasmas as a phenomenological description of their dynamic properties on all scales; observational, theoretical and modelling aspects of collisionless magnetic reconnection; the formation and dynamics of shock waves; and a review and assessment of microprocesses, such as the hierarchy of plasma instabilities, non-local and non-diffusive transport processes and ionisation and radiation processes.  In addition, some of the lessons that have been learned from the extensive existing knowledge of laboratory plasmas as applied to astrophysical problems are also covered.   This volume is aimed at graduate students and researchers active in the areas of cosmic plasmas and space science.   Originally published in Space Science Reviews journal, Vol. 278/2-4, 2013.